The translation of conceptual metaphor in political news - Siriam, Siriam; Widyastuti, Susana (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2023)
Metaphorical expressions (MEs) are abundant in political text and their translation